Designerly Learning: Workshops for schools at the Design Museum - Charman, Helen (Design and Technology Education: An International Journal, 2010)
This paper presents qualitative research recently undertaken by the Head of Learning at the Design Museum. The research explores how learning in the museum’s workshop programme for schools is conceptualised by the museum educators who devise and teach on the programme. The study is framed by an epistemological stance of social constructionism, in view of its relevance to respondents’ accounts of the social, intersubjective nature of learning within the workshops. Based on findings from five semi-structured interviews, the localised nature of the case study considers the distinctive characteristics of learning within a typologically specific museum amidst debate in the cultural sector over the role and status of museum learning more generally. A brief literature review summarises features of professional design practice and of ‘design thinking’ salient to the study, in particular the proactive engagement of design in its realworld context, and a systemised account of designers’ cognitive processes. The interview data is then presented across three themes. These themes are: shared perspectives on the content of learning; on the environment for learning; on the processes of learning. Key findings from the interviews are synthesised into an outline of an ‘ideal-type’ workshop which sets out the core phases and behaviours therein. The term ‘designerly learning’ is coined as a concept that can be adopted to ‘organise the experience of learning’ in the school workshops at the Design Museum (Pring, 2000:10). Notably, designerly learning seeks to model characteristics of design thinking and practice to the learner through the experience of a workshop using the museum’s handling collections. Arguably, it is a concept particular to this institution, rooted in its distinctive disciplinary context of design. In conclusion a note of caution is sounded regarding the theoretical abstraction of the concept of designerly learning, notwithstanding its educational and professional value as an “adequate, simplifying paradigm” of learning (Cross, 1992).